EXPERIMENTAL INVESTIGATIONS OF THE HYDROTHERMAL GEOCHEMISTRY OF PLATINUM AND PALLADIUM: V. EQUILIBRIA BETWEEN PLATINUM METAL, PT(II), AND PT(IV) CHLORIDE COMPLEXES AT 25 TO 300OC - Gammons C.H. (My University, 1996)
The solubility of metallic Pt in HCl solutions was determined at 200 to 300°C at oxidation states buffered near the aqueous Pt(II)/Pt(IV) boundary. Equilibrium constants were obtained for the following disproportionation reactions: log K, 200° 250° 300°C 2PtCl42− = PtCl42− + Pt(s) + 2Cl− 1.47 1.70 1.54 (a) 2PtCl3− = PtCl5− + Pt(s) + Cl− 1.77 1.74 1.37 (b) with experimental uncertainties of approximately ±0.20 log units. These results are found to be in good agreement with previously published estimates for reaction at 60 to 152.5°C. The data indicate that the relative stability of the Pt(II) and Pt(IV) chloride complexes does not change appreciably with temperature. This is in contrast to previous work in the Au(0)/Au(I)/Au(III) system which demonstrates that the Au(I) chloride complexes are unstable with respect to Au (III) at low temperature, but become the dominant aqueous species at 300°C.Pt(IV) chloride complexes are unlikely to be important in high temperature hydrothermal fluids, as unrealistically high aqueous platinum concentrations are required to stabilize these species relative to Pt(II). In contrast, thermodynamic calculations suggest that Pt(IV) chloride or hydroxychloride complexes may be the dominant form of dissolved platinum in low temperature brines that are strongly oxidized (e.g., seawater). In oxygenated, Cl-rich solutions, the solubility of Pt is extremely high at pH < 6, such that the mobility of this metal will most likely be limited by surface adsorption reactions and/ or its abundance and rate of dissolution in the enclosing rock or soil. At neutral to alkaline pH, calculated solubilities are much lower, and saturation with Pt oxide phases may occur, as has recently been described in nature.